Interactivity Model 2.0: Social communication dynamics in organizational contexts (2016)
This article presents the Interactivity Model 2.0, which aims to support the communicative process of knowledge transfer 2.0 developed in organizations that follow a social business model. This model has its origin in SECI and Ba interaction models and in the Open Communication Interactivity Model. This study defines Interactivity building on two concepts: role and interaction. The study considers role as actors taking part in Knowledge Transfer Process 2.0, and interaction as the process of communication that enables a transfer. The research tests this model through a case study at a Colombian Information Technology Company. The results show the changes of the communicative process in social settings and allow the identification of a message, a role, the direction and control of a message, and the knowledge contributions of the various actors of the Knowledge Transfer Process 2.0. © 2016.